Green finance and local wisdom synergy in enhancing community-based drinking water sustainability - I Gusti Ayu Lia Yasmita; Ni Luh Laksmi Rahmantari (Bioculture Journal, 2026)
Background: Access to safe drinking water remains a challenge in Sukadana Village due to geographic conditions, limited infrastructure, and financial constraints. The Danu Kerthi concept, rooted in Tri Hita Karana, promotes sustainable water management by balancing human, environmental, and spiritual aspects. Green finance, through green bonds and Pay-As-You-Go (PAYG) schemes, enhances financial sustainability. Integrating these approaches with technology can ensure long-term water access through community, government, and private sector collaboration. Methods: This study uses a descriptive qualitative approach to explore phenomena related to access, management, and challenges of community-based drinking water sustainability in Sukadana Village, Karangasem. The data collection technique was carried out through in-depth interviews with 30 respondents who were selected using the purposive sampling method. The data obtained was analyzed inductively to identify relevant patterns and themes. Findings: Data were analyzed to identify key components and organized into specific indicators and sub-indicators, forming a comprehensive model for sustainable system development. The resulting framework includes aspects such as access to clean water, management systems, financial sustainability through green finance, challenges faced, and strategies grounded in local wisdom (Danu Kerthi concept). These findings are systematically presented to guide future policy and implementation efforts for resilient and inclusive water management systems. Conclusion: The creation of a well-defined and systematic model offers a practical foundation for improving the sustainability, resilience, and inclusiveness of water management, particularly in rural and culturally traditional communities. Integrating green finance with local wisdom, as reflected in the Danu Kerthi concept, enhances the long-term viability of community-based drinking water systems, as exemplified by the model implemented in Sukadana Village, Karangasem, Bali. Novelty/Originality of this article: This study intoduces a new approach to community based drinking water management by integrating the Danu Kerthi concept with green finance through Pay-As-You-Go (PAYG) for sustainable funding.